PROJECT-BASED LEARNING WITH MIND MAPPING: A PEDAGOGICAL APPROACH TO ENHANCE ENGLISH WRITING SKILLS - Sumbulatin Miatu Khabbah; Rahmat Budiman; Widya Rizky Pratiwi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Writing is an important ability in English study, yet many students fail to communicate their thoughts coherently and artistically. Innovative solutions are required to assist kids in enhancing their writing skills. The purpose of this study is to look into the usefulness of Project-Based Learning (PjBL) combined with mind mapping in enhancing students' writing skills, specifically in recount texts. Using a pre-experimental research methodology, the study was conducted at SMKN 1 Pangkalan Banteng with 28 eleventh-grade students from class XI AKL 1. The study had three stages: pre-test, treatment, and post-test. The students' pre-test average score was 71.04, which increased to 78.32 in the post-test. The data were examined using a normality test and a paired sample t-test. The normality test validated the data's normal distribution. The paired sample t-test resulted in a significant difference (p-value < 0.05) between pre-test and post-test scores. These data indicate that Project-Based Learning with Mind Mapping is an effective way to improve students' writing skills, particularly in writing recount texts. This study contributes to the field of English language instruction by emphasizing the advantages of integrating innovative and student-centered methods to improve writing skills.